Personalization of politics: a definition proposal for a systematic study - Rebolledo, Marta (2017)
Despite the relevance of personalization in research in Political Communication, as well as other fields of study, there is a state of confusion in the literature on the concept. The main reason is that there is no consensus around a widely shared definition. In addition, the personalization of politics can be approached from different perspectives, corresponding to the main actors involved in the political processes, that is, the media system, the political system and the citizens. Consequently, the results and conclusions are varied and, even occasionally, disparate. Therefore, this lack of conceptual clarity represents a limitation for progressing in the study of personalization. Hence the aim of this research is to propose a definition serving as a reference for further studies on this phenomenon.